Differences in trunk-shoulder inter-joint coordination and sequencing between elite and recreational ice hockey players during slap shots - Robbins, S. M.; Renaud, P. J.; MacInnis, N.; Pearsall, D. J. (Sports Engineering, 2023)
There has been limited research examining kinematics during ice hockey slap shots, especially how the body segments are coordinated during this task. The objective of this study was to compare shoulder-trunk inter-joint coordination and sequencing between elite and recreational ice hockey players when completing a slap shot. Eight elite and eight recreational players completed slap shots on real ice. Kinematic data of the trunk, humerus, stick, and puck were collected using a 14-camera motion capture system. Inter-joint coordination between the shoulder and trunk was determined using continuous relative phase, and both magnitude and between-trial variability measures were calculated. To determine sequencing, peak velocity of the shoulder and trunk were determined. Mann-Whitney U tests compared coordination variables and sequencing between elite and recreational players. Elite players were more out-of-phase (i.e., anti-phase) for trunk-rotation/shoulder-elevation plane (p = 0.05) and trunk-rotation/shoulder-elevation (p = 0.03) on the trail side. Elite players had greater between-trial variability for trunk-sideflexion/shoulder-elevation on both lead (p = 0.02) and trail (p = 0.05) sides. Regarding sequencing, peak trunk angular velocity occurred earlier in relation to peak shoulder (trail side) angular velocity (p = 0.04) for elite players. The out-of-phase and greater coordination variability in elite players may allow them to adapt more easily to varying shot environments. The proximal to distal sequence might help them to produce faster puck speeds.